2023
DOI: 10.1186/s13030-023-00282-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism mediates the association between childhood abuse and the well-being of community dwelling adult volunteers

Abstract: Background Previous studies reported that the experience of maltreatment in childhood reduces subjective well-being in adulthood and that neuroticism is negatively associated with subjective well-being. However, the interrelationship between childhood maltreatment, adult life events, neuroticism, and subjective well-being has not been analyzed to date. Methods A total of 404 adult volunteers provided responses to the following questionnaires: 1) Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Consistent with this finding, we previously reported that childhood abuse affects SSS in the general adult population. 14,15,25,26 On the other hand, women who experienced childhood sexual abuse reportedly had a lower objectively evaluated socioeconomic status. 27 Childhood abuse was also associated with lower objective social status expressed by education, income, and employment levels in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, we previously reported that childhood abuse affects SSS in the general adult population. 14,15,25,26 On the other hand, women who experienced childhood sexual abuse reportedly had a lower objectively evaluated socioeconomic status. 27 Childhood abuse was also associated with lower objective social status expressed by education, income, and employment levels in adulthood.…”
Section: Discussionmentioning
confidence: 99%